Management of external component of the public debt of the Western Balkan countries - Despotović, Danijela; Milićević, Srđan; Cvetanović, Slobodan; Nedic, Vladimir (BizInfo Blace, 2023)
The paper examines the external position of the countries of the Western Balkans using the movement of external liquidity indicators (Debt service/Export good and services and Debt service/gross national product (GNI)) and external solvency indicators (External debt/GNI and External debt/Export good and services) ) in the period 1999-2021. according to the criteria of the World Bank. In order to assess the external position of these countries, the level of the calculated external liquidity and external solvency indicators is compared with the identical indicators of Bulgaria, also a Balkan country but a member of the European Union since 2007. The paper noted a certain improvement in the external liquidity and external solvency of the countries of the Western Balkans, from 2010 to 2021, except for Montenegro, where in recent years there has been a multiple increase in the Eternal debt / GDP indicator. Also, based on the observed indicators, it was concluded from the perspective of the limits of external liquidity and external solvency determined by the World Bank that the Western Balkan countries are not threatened by the possibility of external illiquidity and external insolvency, except in Montenegro.